Does employee representation foster workplace democracy? - Uwe Jirjahn; Johannes Kiess (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
From a theoretical viewpoint it is not clear whether or not works councils contribute to workplace democracy. This study is the first to provide systematic evidence that employees in establishments with a works council experience more democracy at work than the ones in establishments without a works councils. Employees' unionization plays an important moderating role in the link between works councils and workplace democracy. The influence of works council presence on experienced democracy at work is more pronounced and much stronger for union members than for nonmembers.
Keywords: J52; J53; M12; O35; 330; Works councils; unions; democratic experience at work; open organizational climate; self-efficacy; collective efficacy